The Influence of Training and Career Development on Performance through the Competence of Employees of PT. Pertamina International Refinery RU VII Kasim Sorong West Papua - Williamson Amamehi; Justine Tanuwijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of HR development practices in the form of training and development on employee competence, analyze the influence of HR development practices in the form of training and career development through organizational learning culture on employee competence, analyze the effect of competence on employee performance and analyze the effect of employee performance to turnover intention. Design/methodology/approach This study uses a quantitative approach sourced from primary and secondary data. The research population was 120 employees, the sample was determined using the Slovin formula, obtained by 92 respondents. Data analysis used validity and reliability test, classical assumption test, multiple linear regression analysis, Sobel test, simple regression and research hypothesis testing. Practical implications. This study recommends that the company PT. Pertamina International Refinery RU VII Kasim Sorong West Papua provides training and career development to each employee continuously so that it has an impact on increasing competence and performance. Originality/value. This study found that employee performance has a negative and significant effect on turnover intention, that is, if employee performance decreases, then employees will get turnover intention.